2004
DOI: 10.1080/09553000400005486
|View full text |Cite
|
Sign up to set email alerts
|

Comparative tissue uptake and cellular deposition of three different plutonium chemical forms in rats

Abstract: Distinct Pu behaviour was observed for biokinetics, retention and liver distribution. The large differences noted between citrate, nitrate and phytate might be explained by differences in systemic and hepatic transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Most studies on lanthanides were conducted before the 1970's; at that time our ability to detect subcellular distribution and biotransformations of these elements was much less than today. However, even a few of the more modern examples of these studies (e.g., uptake of Pu of different oxidation states in mice [Fouillit et al, 2004] and in the cells in culture [Planasbohne and Duffield, 1988]) give no detailed account of the exact intracellular localization and speciation.…”
Section: Discovery Of Accidental or Otherwise Unintentional Introductmentioning
confidence: 99%
“…Most studies on lanthanides were conducted before the 1970's; at that time our ability to detect subcellular distribution and biotransformations of these elements was much less than today. However, even a few of the more modern examples of these studies (e.g., uptake of Pu of different oxidation states in mice [Fouillit et al, 2004] and in the cells in culture [Planasbohne and Duffield, 1988]) give no detailed account of the exact intracellular localization and speciation.…”
Section: Discovery Of Accidental or Otherwise Unintentional Introductmentioning
confidence: 99%
“…Several reviews [13,14,19,20] present the possible transfer mechanisms of Np(V), Pu(IV) and Am(III) from blood to liver cells, and describe possible time-and mass-dependent binding of these actinides in the liver cells with high molecular weight proteins such as calmodulin, ferritin and lipofuscin. It has also been shown [21] that hepatocyte cells concentrate more plutonium than sinusoidal cells and that Kuppfer cells play an important role in the phagocytosis of polymeric forms of plutonium.…”
Section: Main Actinides' Biological Ligandsmentioning
confidence: 99%
“…Most actinide studies were carried out with actinides in higher oxidation states, especially with uranium(VI) (Carrière et al, 2004(Carrière et al, , 2005aMilgram et al, 2008aMilgram et al, , 2007Milgram et al, , 2008bMirto et al, 1999a,b;Muller et al, 2006;Rouas et al, 2010), for which the relationship between its speciation and its cytotoxicity onto mammalian cells is comprehensively studied. A second, well studied actinide is plutonium(IV), whose uptake and binding was studied with various cell lines Fouillit et al, 2004;Gorman-Lewis et al, 2011;Jensen et al, 2012Jensen et al, , 2011Planas-Bohne and Duffield, 1988;Planas-Bohne et al, 1985Planas-Bohne and Rau, 1990;Schuler and Taylor, 1987). For trivalent actinides, the chemical analogs of lanthanides, no studies concerning their biological interactions are reported up to date.…”
Section: Introductionmentioning
confidence: 99%